Corticotropin-releasing hormone inhibits autophagy by suppressing PTEN to promote apoptosis in dermal papilla cells - Wenzi Liang; Xiuwen Chen; Na Ni; Chutong Zhuang; Zhiying Yu; Ziqing Xu; Yingshi Li; Changmin Lin; Keng Huang (Annals of Medicine)
Background Stress-related hair loss is on the rise, largely due to escalating levels of stress-related corticotropin-releasing hormone (CRH) through poorly defined mechanisms. CRH-mediated activation of corticotropin-releasing hormone receptors (CRHRs) on dermal papilla cells (DPCs) is a likely cause of stress-related hair loss. The aim of the study is to elucidate the key mechanisms of alopecia caused by CRH and provide potential new targets for the treatment of stress-related hair loss.Methods 4D label-free quantitative proteomics of DPCs and the chronic unpredictable mild stress mouse (CUMS) model were used to explore the relationship and mechanism between CRH, DPCs and hair regeneration.Results CRH initially downregulated PTEN to suppress autophagy, leading to DPC apoptosis. Overexpression of PTEN enhanced autophagy and mitigated CRH-dependent DPC apoptosis. CRH inhibited PTEN and activated the PI3K/AKT/mTOR pathway, whereas rapamycin inhibited this pathway and activated autophagy, consequently lowering apoptosis, suggesting that increased susceptibility to apoptosis is caused by decreased autophagy. CUMS-induced hair growth disruption is accompanied by an increase in CRHRs and a decrease in PTEN levels within the dermal papilla. Intracutaneous injection of CRH impeded hair regeneration and decreased PTEN in mice, concurrent with inhibition of autophagy and increased apoptosis.Conclusions These findings indicate that PTEN loss coupled with PI3K/AKT/mTOR-mediated autophagy inhibition and apoptosis in DPCs is a key mechanism of stress-related hair loss induced by CRH and suggests that topical activation of PTEN or enhancement of autophagy, e.g. through rapamycin, may have a therapeutic effect on stress-induced hair loss disorders such as alopecia.